El desarrollo rural y su repercución en las migraciones juveniles: Caso específico: Comunidad rural de Poroto, año 2016 - Morillas Vargas, Katherine Lauly (2017)
The present research looks for the analysis of the rural migration of the young population of the Rural Community of Poroto in the year 2016. For this it was used the descriptive design with the application of a structured survey in such a way that, the current situation of Rural youth in the educational, labor and social participation within the community. Under the assumption that current development factors in rural communities in the country determine youth migration, indicators of development such as literacy rate and schooling, employment rate and income level, and participation in social or political. It was also determined, based on the expectations of rural young people in the Community, the rate of migration of these to the city. As a result, it was demonstrated that the current factors of the development model are those that determine the mobilization of the youth population from the countryside to the city. Finally, the necessary measures were proposed through the elaboration of pertinent policies to improve the context within the community, according to their characteristics and needs; Under the New Rural Development approach. That is, young people from the countryside as the strategic actors of their own development.